Technical challenges of intracellular flow cytometry-based assays as a functional complement to diagnosis of signaling defects of inborn errors of immunity: PI3K pathway as a case of study - del Pino Molina, Lucía; Reche Yebra, Keren; Soto Serrano, Yolanda; Clemente Bernal, Álvaro; Avendaño-Monje, Carmen L.; Ocejo-Vinyals, J. Gonzalo; Rodríguez Pena, Rebeca; López Granados, Eduardo (Frontiers in Immunology, 2024)
BackgroundThe use of next-generation sequencing in inborn errors of immunity (IEI) has considerably increased the identification of novel gene variants, many of which are identified in patients without the described clinical phenotype or with variants of uncertain pathogenic significance in previously described genes. Properly designed functional and cellular assays, many necessarily accomplished by research-based laboratories, reveal the pathogenic consequences of the gene variants and contribute to diagnosis. Activated PI3Kδ syndrome (APDS) is a rare disease that can be divided into APDS1, caused by gain of function (GOF) mutations in PIK3CD gene, and APDS2, with loss of function (LOF) variants in the PIK3R1 gene. Both entities present hyperactivation of the PI3K pathway, which can be analyzed through Akt and S6 phosphorylation status.MethodsOur objective was to perform an accurate, robust, and reproducible functional assay to analyze the phosphorylation status of proteins in the PI3K-Akt-S6 pathway by flow cytometry, to contribute to diagnosis, to monitor treatments, and to establish intra-assay standardization.ResultsWe illustrate the robustness and reproducibility of our experimental procedure in patients with APDS who had high Akt and/or S6 phosphorylation levels at baseline, and after anti-IgM stimulation in B cells. We show the relevance of an appropriate cohort of samples from healthy donors, processed within the same conditions as the suspected samples, in particular the time frame for sample processing once blood is collected.DiscussionWe highlight the importance of B cell stimulation through B cell receptor signaling, which is highly recommended, especially for samples that would be processed more than 24 hours after blood extraction. Also, having a defined experimental procedure is important, including the cytometer setup, which allows cytometer reproducibility for a period of time, enabling the comparison of a sample at different times.